2015
DOI: 10.1186/s13104-015-1558-1
|View full text |Cite
|
Sign up to set email alerts
|

Occupational sunscreen use among US Hispanic outdoor workers

Abstract: BackgroundOccupational ultraviolet radiation (UVR) exposure is a risk factor for skin cancer, and Hispanic individuals are over-represented in a number of outdoor occupations (e.g., farming, landscaping). This study examined predictors of occupational sunscreen use in a group of US Hispanic adults who work outdoors.ResultsA population-based sample of outdoor workers (n = 149, 85 % male) completed survey measures regarding their demographics, melanoma risk, perceived skin cancer risk, skin cancer knowledge, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
26
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 23 publications
5
26
0
Order By: Relevance
“…The findings of our study for secondary prevention are consistent with previous studies in mountain guides: about 66% of mountain guides in this study had never attended a skin cancer screening before, compared to about 50% in other studies. Consistent with previous studies, 35,40,41 we found a significant association between high perceived skin cancer knowledge and a higher likelihood of undergoing skin cancer screening. 34 Today, 10 years after the introduction of compulsory skin cancer screening in Germany (in 2008), 24 about one-third of the eligible general population has undergone at least one skin cancer screening.…”
Section: Discussionsupporting
confidence: 92%
“…The findings of our study for secondary prevention are consistent with previous studies in mountain guides: about 66% of mountain guides in this study had never attended a skin cancer screening before, compared to about 50% in other studies. Consistent with previous studies, 35,40,41 we found a significant association between high perceived skin cancer knowledge and a higher likelihood of undergoing skin cancer screening. 34 Today, 10 years after the introduction of compulsory skin cancer screening in Germany (in 2008), 24 about one-third of the eligible general population has undergone at least one skin cancer screening.…”
Section: Discussionsupporting
confidence: 92%
“…A range of 21–88% of outdoor workers perceived their skin cancer risk above average . Eighty‐seven per cent of US workers stated skin cancer as a serious disease, and 43% believed they would develop skin cancer during their lifetime …”
Section: Resultsmentioning
confidence: 99%
“…41,42 Twenty-two per cent of Latino migrant farmworkers in the USA had never heard of skin cancer before. 42 Agricultural workers from Switzerland 43 and US state park workers 44 showed high knowledge related to skin health, whereas US Hispanic outdoor workers 45 , Latino day labourers 46 and Irish golf course maintenance workers 47 had insufficient skin cancer knowledge.…”
Section: Sun-related Knowledge and Awarenessmentioning
confidence: 99%
See 1 more Smart Citation
“…Only about a quarter of Latino postal workers in California reported using a wide-brimmed hat or sunscreen [52]. A more recent survey of US Hispanic outdoor workers across 5 southern and western states found low reported use of sunscreen, hats and protective clothing, with nearly 70% rarely or never using sunscreen, fewer than 20% wearing clothing or a hat to cover the face and neck, and only 40% wearing clothing to cover their arms while working outside [53]. Policy and educational interventions at outdoor worksites have been effective at increasing sun protective behaviors of workers [49], but it will be important to adapt these interventions to reach Hispanics of low English literacy [50].…”
Section: Discussionmentioning
confidence: 99%